PENGARUH CORPORATE SOCIAL RESPONSIBILITY, PROFITABILITAS, KEBIJAKAN DIVIDEN, UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Yahdiyani, Azka; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to examine the influence of corporate social responsibility, profitability, dividend policy, and firm size to the firm value. The research object is chemical and basic industry companies which are listed in Indonesia Stock Exchange in 2013-2015 periods, the sample collection has been done by using purposive sampling method. The statistic test instrument which has been applied to determine regression model equation, classic assumption test, model feasibility test, and t-test is the SPSS 20 program. The result of the research shows that corporate social responsibility give positive and insignificant influence to the firm value. This condition shows that the company has not been able to communicate the social responsibility appriopriately yet. Meanwhile, profitablity and firm size gives positive and significant influence to the firm value. This condition shows that high profitability which has been gained by the company and the size of the firm size can enhance the firm value. Meanwhile, dividend policy give positive and insignificant value to the firm value. This condition shows that the enhancement of dividend is not always followed by the enhancement of firm value.Keywords: Corporate social responsibility, profitability, dividend policy, firm size, firm value.